Effect of Laser Vocal Cord Surgery under Laryngeal Microscope Combined with Nano-silver Dressing Antibacterial Nursing on Efficacy and Quality of Life of Patients with Laryngeal Cancer: Nano-silver Dressing Antibacterial Nursing and Laryngeal Cancer - Zhu, Xiangyue; Li, Qianqian; Li, Jianzhi; Zhang, Xiaohong; Xiao, Hong (Cellular and Molecular Biology, 2022)
To explore the adoption effect of nano-silver medical antibacterial dressing in the perioperative treatment of patients with laryngeal cancer, 120 patients with early laryngeal cancer were selected as the research objects. According to the different treatments, they were averagely divided into the test group (laser vocal cord surgery under a laryngeal microscope and nano-silver medical antibacterial dressing) and the control group (laser vocal cord surgery under a laryngeal microscope and sterilized vaseline gauze). The results showed that there were considerable differences in dressing-change times, dressing-change cost, hospital stay, and recovery time between both groups (P<0.05). The number of mild pain cases in the test group was more than that in the control group at 1, 3, and 5 days after surgery, with statistically considerable differences (P<0.05). There were substantial differences in wound area between the two groups at 3 and 5 days after surgery, and the test group was larger than the control group (P<0.05). In the test group, 0 patients had postoperative reinfection, wound dehiscence, and wound hernia. In the control group, 3 patients had postoperative reinfection, 1 had wound dehiscence, and 1 had wound hernia. In summary, compared with traditional sterilized vaseline gauze, the nano-silver medical antibacterial dressing could reduce postoperative dressing pain and promote the recovery of wounds, thus shortening the hospital stay and improving the quality of life of patients after surgery.